Pembingkaian Media Dalam Perpektif Hak Asasi Manusia Terhadap Kasus Intoleransi Beragama dan Berkeyakinan di Masa Pandemi - Hafiz, Mohamad; Rusman, Acep Muhamad (Universitas Djuanda Bogor, 2024)
Coverage of the issue of violations Religion and Belief Freedom during the pandemic is not free from the bias of journalists and mass media. The issue, which is reported inaccurately and sometimes tends to sharpen existing differences in society. It should then be able to provide an overview to the public on how to understand differences amidst the pandemic. Detik.com, as a popular mainstream online media in Indonesia, has the advantage of distributing news quickly. Coverage of the issue of violations is quite common in detik.com. This study focuses on examining how the news texts regarding the issue during pandemic are constructed by detik.com using the framing analysis method of Zhongdang Pan and Gerald M. Kosicki. In this study, the researcher uses the theory of the construction of social reality and views it from the perspective of Human Rights. This aims to see how detik.com constructs its news texts regarding the issue during the pandemic. Based on the research results, detik.com tends to be more biased towards the victims, as seen from most prominent structural units emphasized by detik.com when constructing news texts regarding the issue violations, such as headlines, leads, background information, quotes from sources, statements, details, and lexicon.